The Merit-based Incentive Payment System: Pearson’s Chi-Square and Categorical Dependent Variable Models Analyzed for Domains---Effective Clinical Care and Efficiency/Cost Reduction - Amrita Shenoy (Journal of Health Economics and Outcomes Research, 2021)
# Background Following the 2015 repeal of the Sustainable Growth Rate formula, the US Centers for Medicare & Medicaid Services' formula under which physicians were reimbursed, two payment systems were put in place to incentivize physicians, one of which was the Merit-based Incentive Payment System (MIPS). MIPS emphasizes high-quality care that is accessible, affordable, and supports a healthier population.